KAJIAN HUKUM TERHADAP PEMBATALAN SERTIFIKAT HGB YANG DIKELUARKAN OLEH BADAN PERTANAHAN NASIONAL KOTA BALIKPAPAN DENGAN NOMOR.6729/KEL.SEPINGGANG TAHUN 2006 DAN NOMOR.6730/KEL.SEPINGGAN TAHUN 2006 YANG TERLETAK DI KOTA BALIKPAPAN SESUAI PUTUSAN NOMOR.05/G/2014/PTUN-SMD - Linda Setia Ningsih; Parlindungan Pasaribu (Yuriska: Jurnal Ilmiah Hukum, 2017)
Land has the deepest meaning, for the life of the nation Indonesia considering most people including patterned economy is still agriculture. Increasing land needs of the growing population and increasing other needs related to the land, of it certainly stimulated a desire to obtain legal certainty jamnan or written evidence regarding the rights and obligations of an ownership. In terms of the guarantee or the rule of law to an ownership question is the certificate appeared to still be in aborted in the form of cancellation of the certificate with the problem of defective administration or flawed procedural and implement the Court's Decision is accompanied by a legal basis, therefore the land certificate serves as a tool evidentiary on holding a piece of land. Strong sense means that the land certificate is evidence that it is not the only one, so the certificate of land according to land registration system adopted BAL can still be aborted / canceled along can prove upfront court.